The Survival of Things - Coveny, Eloise Jayne (Auckland University of Technology, 2015)
How might a sonic archiving installation practice produce conditions of history other to orthodox narratives of time? What might a Benjaminian “destructive character” today make of analogue and digital archives for producing uncanny encounters within chips of messianic time? The above dialectical image maps out my research site. At my crossroads stands History proper and historical ambiguity—spoken as ‘I’, my site inscribes difference in archiving things from Victoriana inspired moments, filtered through a girl from Auckland, New Zealand circa 1980s and 1990s (culminating most poignantly in 1994). My installation practice evokes particularly voices materialised through sonic forces aided through photographic, filmic, and recording apparatuses and their representational modalities. These sonic forces material my artistic research practice as a historic figure existing within me as an artist-researcher figuring out (my) different narratives. I employ myself here as a type of destructive (Benjaminian) figure, making radical sonic interventions as historic otherness appear to me to bring to ‘light’ Walter Benjamin’s conceptual historic materialism of time as: the true picture of the past; time at a standstill; moment of danger; ambiguity; dialectical image that is pregnant with tensions; uncanny limits to ourselves. I unpack these radical expressions of time and history—that are marked out above in my dialectical image; my site of research—through the following exegesis. I figure my practice (my self) dangerously between the dominance of orthodox archiving narratives to specify an acute ‘familiar’ moment—say 1994 (1994: Time-space encounters between digital forces and analogue ghosts). I read my project as the dialectical image above and hope that one can better understand this site increasingly throughout the reading of this exegesis. This understanding of time at a [dialectical] standstill is taken from the philosopher Walter Benjamin. This time of arrest is counter to linear time that is often posed as the dominant voice throughout historicism [discourses] (i.e. writing history) that marginalises other voices and other experiences. My practice works within this site of investigation to privilege lost voices that explore a longing for historic authenticity—where the location of authenticity lies in its alterity, in what is distant to the present time and space. Benjamin practices [destructive] lyrical configuration through the modern allegory, which I here explore through my practice in the form of anachronistic spatial configuration (installation) as a method for [sonic] archiving. The anachronistic structuring of my installation tests activate dialectical tensions that speak to us of the hidden voices repressed by the orthodox structure of things; through juxtaposing and rupturing orthodox histories via my relations to things in the world. This has become in part an autobiographical tenor that lyrically composes my exegesis and installation as a methodology. It does this bearing in mind the viewer’s independence, where my own autos is largely heterogeneously fractured into the archival installation final exhibition aiming for uncanny registers that can only be designed by the ‘hand’ of weak messianic power (Benjamin). My sonic forces mapping out the research aims of this installation archiving practice are inspired primarily by the work of Walter Benjamin's concept of Messianic time in relation to historical materialism. My artistic research has focused in on relations of voices through time; voices that have spoken to me throughout (auto)biographical encounters with artefacts; things that continue to return and inhabit me more so than I realise. These things are speaking to me now, here; at a crux moment of a self-splitting between some fantasy autos of my biography, and yet they are shot through with the voices of those philosophers I am engaging and their autos. In this sense, my artistic material and precedence gather around the literary, poetic, and mystical voices of others (people, antiques, commodities, spaces, places, photographs, films and other textual forms of archival material). The images that make up my work emerge from the imagination, now brought to the fore through these textual methodological encounters that inspire my way through. In this sense, my practice appears on the surface to be voiding the proper of art historical practitioner precedence, and yet in this way I have followed an authentic (unorthodox) path that is akin to the destructive character Benjamin evokes. The images of others sit below this surface only to rise uncannily in the strange present that this time evokes. The concept of the uncanny, guided by voices of Martin Heidegger, Sigmund Freud and Walter Benjamin, open up my mystical moments for installing such an encounter of strange time as a survival of things.
Keywords: Archive; Time